From Non-Alignment to Multi-Alignment: India Hopes to Contain China - Sehgal, M. L. (Advances in Social Sciences Research Journal, 2020)
In 1954, India did a ‘Himalayan Blunder’ of having fallen into China’s trap of accepting Tibet to be a part of China. In ‘1962 Indo- China War’, China’s biggest argument of its having claim over Ladakh was that since Ladakh was a part of Tibet and thus belongs to China. But the historical perspective, altogether, contradicts it. Having annexed Tibet and forcefully occupying Aksai Chin, there was no looking back for China; be it in 1965, 1967, 1987, 2013, 2017; and now in 2020. Every time, the Chinese rulers would invent one lie or the other. Xi Jinping, the present Chinese President, imbibes the qualities of both- Mao Tse Tung, Chinese ideologue, a protagonist of the ‘Expansionist Ideology’ and the philosopher- Sun Yat-sen who wrote “The Art of War” and believed that“The greatest victory is that which requires no battle”. Xi Jinping is an expert in both. He did ‘land grabbing’ not just of India and Tibet rather China has 17 territorial disputes with its neighbours, on land and sea. He has also applied ‘Debt- Diplomacy’; mostly on the nascent, economically weak, fragile democracies to subjugate them without firing a bullet. What to talk of entrapping India’s immediate friendly neighbours under his ‘Debt-net’ by using it as a political ideology called “String of Pearls” (weaning away friendly Indian neighbours with the money power), China has loaned over 1.5 trillion(5% of its GDP) to more than 150 countries that make it a bigger lender than even W.B. and IMF that compares it well with the USA. China’s stance along LAC fits well with a larger pattern of the ‘Expansionist Ideology of Mao. Modi, unlike Nehru, chose to follow Multi-Alignment and befriended countries both the Indian Ocean Region (IOR) and the South China Sea lying in the periphery of China by garlanding China with a ‘Necklace of Diamonds’ which gave India the strategic access and fast-developing routes to Central Asians, East Asian and South-East Asian countries. Moreover, the USA, India, Australia and Japan formed ‘The Quadrilateral Security Dialogue QUAD’ in case of any emergency. India’s ‘Look East Policy; has paid it the dividends with the USA openly playing the role of a deterrent to China in South China; Australia gave a military base in Cocos Islands, France supplied Rafales and good-humoured Russia, unlike the Russia of 1962, is supplying India with the much needed Military pieces of Equipment while refusing the S-400 to China. The suspected role of China in the pandemic COVID-19 has made it ‘a persona non- grata’ in the eyes of many countries. The anti-democracy Security Law in Hong Kong and the USA’s open support to the ‘Independent Tibet’ and recognizing ‘Taiwan as a Sovereign State’ has threatened ‘One China Principle’ which has resulted in the taming China by India.